Comparison of the physical education & sports teachers’ educational research attitudes with other teachers - Fatih Özgül; Murat Kangalgil; Rahmi Yıldız (Journal of Education and Learning (EduLearn), 2021)
The aim of this research was to compare the attitudes of physical education and sports teachers and other branch teachers towards educational research. The sample group of the study was determined by convenient sampling method. The data of the study were collected from 304 teachers in different fields (152 Female, 152 Male; 102 of them are in 23-29 age group, 131 of them are in 30-36 age group and 71 of them are above 37 years). In the research, "Attitude Scale for Educational Researches" was used. The Cronbach Alpha value of the scale was calculated as .87. In the analysis of the data, SPSS (ver.22.0) program was used. Since the data were normally distributed (Kolmogorov-Smirnov), t test, ANOVA and Tukey test were applied and level of significance taken as .05. The total scores of the teachers were compared according to some variables in the study. As a result that the teachers’ attitudes towards educational researches found to be a high level in the study. The female teachers’ attitudes were found to be higher than the male teachers’ towards educational research. The attitudes of the teachers were compared in terms of the branches towards educational researches and there was not found any significant difference between them.